Programma: Vondelpark openluchttheater 1-7 juli: georganiseerd in het kader van de Zomeruniversiteit Vrouwenstudies (1981)
Programma: Vondelpark openluchttheater 1-7 juli: georganiseerd in het kader van de Zomeruniversiteit Vrouwenstudies.